Spatial patterns of prokaryotic communities in kettle hole soils follow soil horizonation - Frindte, Katharina; Kolb, Steffen; Sommer, Michael; Augustin, Jürgen; Knief, Claudia (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2023)
Kettle holes are small lentic wetlands <1 ha that are often embedded in agricultural landscapes. These small landscape elements are influenced by their surroundings, as fertilizers and eroded soils are transported into these wetlands. Further, kettle holes often display highly variable water tables, resulting in differences in soil development and spatiotemporal habitat changes. The impact of these spatial heterogeneities of kettle hole soils on prokaryotic communities remains mostly unknown. In this study, we collected soil cores from different positions within a kettle hole and the adjacent farmland. The soil cores were divided into different horizons due to soil development and erosion processes. Basic soil parameters were determined and prokaryotic community analysis was performed based on 16S rRNA gene amplicon sequencing and qPCR. The results indicate that prokaryotic communities were only weakly differentiated by landscape element (PERMANOVA R2 = 0.08, P = 0.001), but showed a clear pattern according to soil horizons (R2 = 0.28, P = 0.001), though not to soil depth. Overall, the organic-rich horizons hosted prokaryotic communities with a significantly higher abundance and richness compared to mineral soil horizons. The mineral horizons that were groundwater-influenced harbored communities that were most similar to the ones in organic-rich peaty horizons. Like the peaty horizons, these colluvial horizons harbored high relative abundances of taxa being associated with different redox-sensitive biogeochemical cycles, including Geobacteraceae, Nitrosomonadaceae, Nitrospiraceae and Desulfobacterota. This indicates, that microorganisms contributing to biogeochemical processes find ideal conditions in these horizons due to fluctuating water levels and thus fluctuating redox conditions. Our findings indicate that small-scale heterogeneities in kettle holes are relevant for the localization of microorganisms being involved in different biogeochemical cycles. This heterogeneity needs to be considered when evaluating the ecological relevance of kettle holes as landscape elements.